Management Logistics Maritime: A Literature Review - Barasa, Larsen; Purba, Damoyanto (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
Using a systematic literature review as the primary research approach, the purpose of this study is to provide an overview of the research trends connected to management of maritime logistics in both Asia and Indonesia. The literature review was carried out with the help of Leximancer, which is a text analytics software, in order to determine the major ideas and recurring topics that were addressed in the research that were chosen. A form of research known as a systematic literature review was utilized for this particular investigation. According to the findings of the comprehensive evaluation of the relevant literature, researchers in Asia and Indonesia follow comparable lines of enquiry in the field of maritime logistics management research. The studies concentrate their attention particularly on topics like the management of supply chains, the optimization of transportation, and the promotion of sustainability in maritime logistics. In spite of the fact that the study tendencies in Asia and Indonesia are quite comparable to one another, certain studies in Indonesia place a distinct emphasis on particular ideas like society, the environment, and marine development. Taking into account its archipelagic character, local rules, and vital position in international trade, these ideas are reflective of the particular challenges and opportunities that Indonesia has when it comes to the management of its maritime logistics. To summarize, Asian research on logistics and maritime management focuses on risks, performance, globalization, environmental sustainability, and green practices. Therefore, Asian trends can be utilized by Indonesian scholars in their studies of maritime logistics management.